Fungal Profile of Vulvovaginal Candidiasis in a Tertiary Care Hospital - Krishnapriya Kalaiarasan; Rakesh Singh; Latha Chaturvedula (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Vulvovaginal Candidiasis (VVC) is a common medical health problem of adult women. It is most commonly caused by Candida albicans. But there is a change in fungal profile. Sabouraud’s Dextrose Agar (SDA) is the most common culture medium used where mixed fungal infection may be missed. It can be detected easily by using chromogenic culture medium. Aim: To know the fungal profile of vulvovaginal candidiasis using Candida CHROMagar and antifungal susceptibility pattern in patients attending tertiary care hospital. Materials and Methods: Culture confirmed cases of VVC presented at Department of Obstetrics and Gynaecology of Jawaharlal Institute of Postgraduate Medical Education and Research (JIPMER), Puducherry, India, from July 2015 to December 2015 were included in the cross-sectional study. Two high vaginal swabs were collected and inoculated on SDA and Candida CHROMagar (Hi-Media, Mumbai, India). After overnight incubation the colonies were counted and colour of the colonies were recorded from Candida CHROMagar. Candida spp. were identified by sugar fermentation and assimilation tests and other conventional tests. Antifungal susceptibility tests were performed by the disc diffusion method using fluconazole (25 µg) and voriconazole (1µg) as per the Clinical and Laboratory Standards Institute (CLSI - M44-A2) guidelines. Results: A total of 50 culture confirmed (23.7%) cases were detected from 211 clinically suspected VVC cases. Candida glabrata (45.1%) was the most common isolate, followed by Candida tropicalis (23.5%), Candida albicans (17.6%), Candida krusei (9.8%) and Candida parapsilosis (3.9%). One mixed infection of C. glabrata and C. albicans was identified on Candida CHROMagar. Mixed fungal infection was observed in 2% of positive culture and 0.5% of VVC cases. The antifungal susceptibility testing revealed that 15.7% and 9.8% isolates of Candida spp. were resistant and Susceptible Dose Dependent (S-DD) respectively to fluconazole. The increase resistant against fluconazole was because of increased isolation of C. glabrata strains. All strains of Candida spp. were susceptible to voriconazole. Conclusion: C. glabrata was the most common causative agent of VVC in a tertiary care hospital. Chromogenic culture medium facilitates detection of mixed fungal infection. In vitro susceptibility testing should be used to guide the treatment especially in cases of non-albicans Candidiasis.